Development of HOTS Assessment Instruments on Newton's Law of Motion by Using Multiple Types of Problems in High School Physics Lessons - Novinta Nurulsari; Undang Rosidin; Eneng Vera Dwi Indriyani (Jurnal Pembelajaran Fisika, 2021)
This study aims to determine the criteria for questions with the type of matchmaking, reasoned plural choice, and causality that can increase HOTS on Newton's Law material about high school physics motion. This research was conducted at MAN 2 Tangerang by using class X, which consisted of two classes. The product developed from this research is the Higher Order Thinking Skills (HOTS) test instrument using Research and Development. The test instruments used were matchmaking, reasoned plural choice, and causality on Newton's Laws of motion in high school physics lessons. Data collection techniques in this development use a questionnaire and Newton's Law of Motion test. The data obtained in the study were analyzed using the Rasch model with the help of Ministep 4.5.1 software. The results showed that the test instrument for higher-order thinking skills on Newton's Law of motion material uses information, pictures, graphics, or data to solve problems, describe information in detail, relate one concept to another, and look for links from different information. can train students' higher-order thinking skills. Keywords: HOTS, Rasch Model, Newton's Laws of MotionDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202101